THE USE OF DIRECT GUIDANCE METHODS IN IMPROVING BIOGRAPHY WRITING SKILLS IN CLASS X - Ririn Ariyanti Fadillah; Hanindya Restu Aulia (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
Learning to write biographical texts for class X students of SMA Negeri 1 Wiradesa has not been well realized because students' interest in writing is lacking, so a method that is not boring is needed. In an effort to improve the skills of writing biographical texts for class X students of SMA Negeri 1 Wiradesa, the direct guidance method was used. This research was conducted through two cycles. Each cycle consists of planning, action, observation, and reflection. The results of this study indicate a process of learning and improvement. This can be seen from the pre-cycle homogeneity value of 72.94, the first cycle of 87.22 and the average value of the second cycle of 90.77. Behavior changes have also changed for the better.